Response of the dog at the early stage of training to verbal commands - Fukuzawa, M.(Azabu Univ., Sagamihara, Kanagawa (Japan)); Uetake, K; Tanaka, T (Animal Behaviour and Management (Japan), 2008)
Since dogs are used for a wide variety of purposes by humans, it is very important to acquire knowledge about their perceptual and learning abilities. In this study, five dogs at the early stage of training were used as subjects to investigate dogs' response to verbal commands; 'Fu-Se' ('Down' in English), 'Ma Te' ('Wait') and 'Ko i'('Come'). Performance markedly was low in tape-recorded command conditions, compared with the two live spoken command conditions (Normal-TT, Normal-EE). The results suggest that dogs at the early stage of training may depend on the direct presentation of live spoken commands by a trainer, however, that they were able to indicate a correct response to the playback command. As for the response of dogs to verbal command at the early stage of training, it is thought that the live spoken command presented by the trainer significantly led to the dog's correct response compared with the playback command.